2017
DOI: 10.4306/pi.2017.14.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Childhood Trauma and Suicidal Ideation: Role of Maltreatment and Potential Mediators

Abstract: ObjectiveChildhood trauma is recognized as an important risk factor in suicidal ideation, however it is not fully understood how the different types of childhood maltreatment influence suicidal ideation nor what variables mediate the relationship between childhood trauma and suicidal ideation. This study examined the path from childhood trauma to suicidal ideation, including potential mediators.MethodsA sample of 211 healthy adults completed the Childhood Trauma Questionnaire (CTQ), Beck scale for Suicidal Ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 56 publications
7
55
1
5
Order By: Relevance
“…However, these data were not included in the final analysis due to excessive amount of missing values. Anxiety and social support mediated the relationship between childhood trauma and suicidal ideation [30]. According to a study with veterans, the protective effect of exercise on suicide risk was mediated by depression, PTSD symptoms, and sleep disturbances [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, these data were not included in the final analysis due to excessive amount of missing values. Anxiety and social support mediated the relationship between childhood trauma and suicidal ideation [30]. According to a study with veterans, the protective effect of exercise on suicide risk was mediated by depression, PTSD symptoms, and sleep disturbances [31].…”
Section: Discussionmentioning
confidence: 99%
“…The review also found that PTSD is rarely mentioned in the literature on suicide, and vice versa; risk of suicide is rarely mentioned in the literature related to trauma [34]. More recent research has indicated a strong link between childhood trauma and an increased risk of suicide [35,36]. Historically such patients have been routinely excluded from PTSD studies as they are perceived as too risky [37], adding to the myth that suicidal patients are not safe to be treated [38].…”
Section: Introductionmentioning
confidence: 99%
“…Физическое насилие над детьми и эмоциональное давление косвенно предсказывают появления суицидальных идей и связаны с тревогой. Игнорирование ребёнка в детском возрасте также косвенно влияет на возникновение суицидальных идей и связано с воспринимаемой социальной поддержкой [10].…”
unclassified